2005
DOI: 10.1128/aem.71.7.3659-3667.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Analysis of the Galactose Phenotype of Dairy Streptococcus thermophilus Strains Reveals Four Different Fermentation Profiles

Abstract: Lactose-limited fermentations of 49 dairy Streptococcus thermophilus strains revealed four distinct fermentation profiles with respect to galactose consumption after lactose depletion. All the strains excreted galactose into the medium during growth on lactose, except for strain IMDOST40, which also displayed extremely high galactokinase (GalK) activity. Among this strain collection eight galactose-positive phenotypes sensu stricto were found and their fermentation characteristics and Leloir enzyme activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 28 publications
3
52
0
Order By: Relevance
“…Most strains of S. thermophilus, including St1-WT and St2-WT, are unable to ferment galactose despite having intact galKTEM genes encoding the required enzymes for the Leloir pathway (19,20) (Table 2). The most likely reason for this phenotype is insufficient transcription due to a defective promoter (19).…”
Section: Discussionmentioning
confidence: 99%
“…Most strains of S. thermophilus, including St1-WT and St2-WT, are unable to ferment galactose despite having intact galKTEM genes encoding the required enzymes for the Leloir pathway (19,20) (Table 2). The most likely reason for this phenotype is insufficient transcription due to a defective promoter (19).…”
Section: Discussionmentioning
confidence: 99%
“…A similar accumulation of galactose in the culture medium is observed when S. thermophilus is grown on lactose, albeit for a different reason. In contrast to L. bulgaricus, S. thermophilus does possess the necessary genes to direct catabolism of galactose, but these genes are generally repressed in the presence of lactose (36).…”
Section: Regulatory Functions: Two Siga Homologues and Relatively Fewmentioning
confidence: 99%
“…bulgaricus and S. thermophilus that are traditionally used together in starter culture mixes. However, it has been shown that many S. thermophilus strains metabolize only glucose, but not galactose [12,13,21,30]. During growth of L. delbrueckii ssp.…”
Section: Introductionmentioning
confidence: 99%